2015
DOI: 10.1016/j.ccell.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Bcl2 BH4 Antagonist for Lung Cancer Therapy

Abstract: SUMMARY The BH4 domain of Bcl2 is required for its antiapoptotic function, thus constituting a promising anticancer target. We identified a small molecule Bcl2-BH4 domain-antagonist (BDA-366) that binds BH4 with high affinity and selectivity. BDA-366-Bcl2 binding induces conformational change in Bcl2 that abrogates its antiapoptotic function, converting it from a survival to a cell death inducer. BDA-366 suppresses growth of lung cancer xenografts derived from cell lines and patient without significant normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
121
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 59 publications
(87 reference statements)
1
121
2
Order By: Relevance
“…A National Cancer Institute (NCI) database library of 300,000 small molecules was docked into the Mcl-1 BH1 structure pocket (aa 256-265) identified by the UCSF DOCK 6.1 program suite for a first round of screening as we previously described (ref. 48 and Figure 8A). The small molecules were ranked according to their energy scores.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A National Cancer Institute (NCI) database library of 300,000 small molecules was docked into the Mcl-1 BH1 structure pocket (aa 256-265) identified by the UCSF DOCK 6.1 program suite for a first round of screening as we previously described (ref. 48 and Figure 8A). The small molecules were ranked according to their energy scores.…”
Section: Discussionmentioning
confidence: 90%
“…Lung cancer xenografts were generated as previously described (48). Six-week-old male nude mice were purchased from Harlan and housed under pathogen-free conditions.…”
mentioning
confidence: 99%
“…A BH3 mimetic, ABT-199, has been developed to selectively bind Bcl-2 and enhances imatinib-induced cell death in chronic myeloid leukemia progenitors (47). BDA-366, a small-molecule Bcl-2-BH4 domain antagonist, can bind BH4 of Bcl-2 with high affinity and selectivity, and this Bcl-2-BH4 antagonist may provide a strategy to improve lung cancer outcome (48).…”
Section: Discussionmentioning
confidence: 99%
“…Although single treatment with GEM or AgNPs induced generation of ROS, AgNPs induced significantly higher levels compared with those induced by GEM ( Figure 7A); this is consistent with previous reports demonstrating that AgNPs induce pronounced cytotoxicity in various types of cancer cells including human breast, ovarian, lung, and germ cells. 24,25,29,60,61 Interestingly, N-acetyl cysteine was able to significantly decrease the levels of ROS that had been induced by GEM, AgNPs, or a combination of GEM and AgNPs, indicating that production of ROS plays a critical role in GEM-and AgNP-induced cytotoxicity. Kovacs et al 31 demonstrated that osteosarcoma cells treated with 20 ÎŒM AgNPs (5 nm) and 85 ÎŒM AgNPs (35 nm) produced considerable levels of ROS; this study additionally confirmed that mitochondrial dysfunction is coupled to oxidative stress.…”
mentioning
confidence: 99%